Environmental perceptions of second home tourism impacts in Finland. Issue 10 (2nd October 2016) - Hiltunen, Mervi J.; Pitkänen, Kati; Halseth, Greg
ABSTRACT: Experiencing nature and enjoying natural amenities have long been identified as key motives for rural second home tourism. However, the more people travel and spend time in the natural environment, the more it is disturbed by their actions and activities. In this paper, we examine how people perceive the environmental impacts of rural second home tourism and how they justify their views. The study focuses on Finland where rural second homes are widespread. Analysis is based on a questionnaire survey conducted among Finns in 2012 ( n = 1189). Responses from different groups of respondents (second home owners, regular users of second homes and non-users) are quantitatively and qualitatively analysed. The results indicate that the Finnish respondents generally think that second home tourism poses some degree of harmful environmental impacts. However, it is the second home owners who are least worried about these environmental impacts. They generally justify their opinions using a "place-related" perspective, that is, by referring to their own experiences and actions at the cottage site. In contrast, the non-users see environmental impacts more often from a broader perspective by referring to the wider environmental interconnections with second home tourism. In our discussion, we introduce the notions of place-based (relative) and phenomenon-based (relational) environmental perceptions as a potential framework for future research on this topic. In mitigating the increasing environmental impacts of second home tourism, understanding the environmental perceptions and awareness of second home owners and users is crucial to be successful in mobilising sustainable options and environmental governance.